Phytochemical Screening of Deep Eutectic Solvent Extract of Butterfly Pea (Clitoria ternatea L.) - Sari, Indah Puspita (Indonesian Journal of Cosmetics, 2024)
This study aims to evaluate the phytochemical content of butterfly pea (Clitoria ternatea L.) extract using the ultrasound-assisted extraction (UAE) method with a deep eutectic solvent (DES) composed of choline chloride and citric acid in a 1:1 molar ratio, with the addition of 10% water. The extraction process was carried out for 30 minutes at a temperature of 50°C. Phytochemical screening results showed that the DES extract of butterfly pea contains various bioactive compounds, including alkaloids, flavonoids, tannins, terpenoids, and saponins, each exhibiting distinct color reactions or precipitates during testing. Flavonoids, particularly anthocyanins, produced a stable red color under acidic conditions and upon interaction with metal ions, indicating potential as natural colorants and antioxidants. Tannins formed dark green complexes with FeCl₃, while terpenoids produced a reddish-brown color as a result of the reaction with Salkowski reagent. Saponins generated stable foam due to their amphiphilic nature, indicating surfactant activity beneficial for cosmetic formulations. Overall, these findings suggest that the DES-based butterfly pea extract holds strong potential as a natural bioactive source for cosmetic applications, particularly due to its prominent flavonoid content and antioxidant activity.